Effect of Some Abiotic Stress Factories on Savrun Spinach (Spinacea oleracea L.) - Nezahat Turfan (Turkish Journal of Agriculture: Food Science and Technology)
In this study were investigated that resistance to salinity, heavy metals, drought and calcerous stress in Savrun (Spinacea oleracea L.) spinach. For this aim, 5-6 leafed seedlings were exposed to NaCl (75, 150 and 225 mM); heavy metals (Fe, Ni and Zn 0.2 mg/L), drought (50%) and 0.2% CaCO3 applications for four weeks half-weekly which plants grown under controlled conditions. Depends on result chlorophyll a, chlorophyll b, total cclorophyll, carotenoids, β-caroten and lycopen increased in drought and CaCO3 treatments. Total soluble protein and GuPX activity were found higher in all stress treatments, proline content increased in NiCl2, 75 ve 150 mM NaCl treatments. While APX activity was higher in 75 mM NaCl and ZnCl2; CAT was higher in 150 mM NaCl and others stres treatments except drought. SOD activity were noted higher in drought, CaCO3 and 225 mM NaCl stresses groups. MDA content was lower in all treatments except FeCl3 and, H2O2 were lower in 225 mM NaCl and drought while it was higher in others. As a result, it was found that tolerance of Savrun spinach is higher to CaCO3 and drought but sensitivity of it is higher to 225 mM NaCl, ZnCl2 and FeCl3. Also it was determined that Savrun genotype is moderate tolerance to NiCl2 and 75 Mm NaCl. However parameters of tolerance to stress that treated on spinach seedling showed variability in Savrun spinach.